Glossário em Libras: uma proposta de terminologia pedagógica (Português-Libras) no curso de administração da UFPel - Friedrich, Márcio Aurélio (2019)
The following master‘s thesis aims to develop a Brazilian Sign Language (Libras) glossary, in the language pair Portuguese – Brazilian Sign Language, focusing on the production of specific sign-terms within the Federal University of Pelotas Business Administration program. This study was originated by a lack of specific terms when considering the interpreting process of the lessons within the aforementioned program; which has been reported by deaf students as well as by sign language translators and interpreters, that needed to choose other translation strategies, such as fingerspelling or the combination of two or more signs. Thereby, the studies of Martins (2018) and Lima (2014) formed the theoretical support of this master‘s thesis. For this study, we elected a quantitative methodology, that has the objective of presenting the frequency, intensity or recurrence of a certain event by numbers, and thus highlighting results that would enable a (re)thinking of the translating practices and an improvement of deaf people and sign language translators and interpreters‘ routine. This way, a research in the Literature of the Business Administration field was carried out in order to identify the most frequent terms, as well as a research with one deaf student from the program. After these steps of investigation were concluded, the final product was created: a Libras glossary of the sign-terms within the Business Administration program of the Federal University of Pelotas, with a sum of 102 sign-terms of 25 words. This glossary offers more efficiency and presents new searching options, such as a QR Code and youtube availability, in which there is access to handshape, palm orientation, movement, facial expressions and location; as well as the formation of the sign-terms considering the Sign Language visual-spatial characteristic.